Calcium signaling mechanisms disrupt the cytoskeleton of primary astrocytes and neurons exposed to diphenylditelluride - Heimfarth, Luana; da Silva Ferreira, Fernanda; Pierozan, Paula; Loureiro, Samanta Oliveira; Mingori, Moara Rodrigues; Moreira, José Cláudio Fonseca; da Rocha, João Batista Teixeira; Pessoa-Pureur, Regina (Biochimica et biophysica acta, 2016)
Diphenylditelluride (PhTe)2 is a potent neurotoxin disrupting the homeostasis of the cytoskeleton. Cultured astrocytes and neurons were incubated with (PhTe)2, receptor antagonists and enzyme inhibitors followed by measurement of the incorporation of [32P]orthophosphate into intermediate filaments (IFs). (PhTe)2 caused hyperphosphorylation of glial fibrillary acidic protein (GFAP), vimentin and neurofilament subunits (NFL, NFM and NFH) from primary astrocytes and neurons, respectively. These mechanisms were mediated by N-methyl-d-aspartate (NMDA) receptors, L-type voltage-dependent calcium channels (L-VDCCs) as well as metabotropic glutamate receptors upstream of phospholipase C (PLC). Upregulated Ca2+ influx activated protein kinase A (PKA) and protein kinase C (PKC) in astrocytes causing hyperphosphorylation of GFAP and vimentin. Hyperphosphorylated (IF) together with RhoA-activated stress fiber formation, disrupted the cytoskeleton leading to altered cell morphology. In neurons, the high intracellular Ca2+ levels activated the MAPKs, Erk and p38MAPK, beyond PKA and PKC, provoking hyperphosphorylation of NFM, NFH and NFL. Our findings support that intracellular Ca2+ is one of the crucial signals that modulate the action of (PhTe)2 in isolated cortical astrocytes and neurons modulating the response of the cytoskeleton against the insult. Cytoskeletal misregulation is associated with neurodegeneration. This compound could be a valuable tool to induce molecular changes similar to those found in different pathologies of the brain. [Display omitted] •Diphenylditelluride disrupts the cytoskeleton of isolated neural cells through calcium signaling.•Diphenylditelluride is a tool to understand mechanisms of neurodegeneration.•Hyperphosphorylation of cytoskeleton modulates the diphenylditelluride insult.